Investigation On Carbon Emission from Energy Usage at Universiti Tun Hussein Onn Malaysia - Ahmad Puad, Fatini; Abdul Kadir, Aeslina; Hassan, Mohd Ikhmal Haqeem; Mohd Yousof, Mohd Fairouz; Al Madhoun, Wesam (International Journal of Integrated Engineering, 2023)
Carbon emissions are the primary contributor to global warming, and it is widely known that the emissions must be decreased significantly to avoid the worst effects of climate change. The objective of this study is to investigate the carbon emissions from energy usage at the Universiti Tun Hussein Onn Malaysia campus. The main data-gathering approach for this study is analyzing technical reports on energy usage from 2015 to 2021 collected at Development and Maintenance Centre (PPP) and Sustainable Campus Office (SCO). The acquired data were evaluated and compared over seven years in data presentation and analysis. According to the findings, the highest energy usage has a significant impact on the rising carbon emission levels on campus, with the maximum emissions occurring in 2015 with 1955.38 tCO2e and the lowest occurring in 2021 with 965.70 tCO2e. On the other hand, based on data collected, according to the building, from 2018 to 2020 the highest building in carbon emission was in 2018 demonstrated the highest carbon emission released by the Faculty of Technical and Vocational Education (FPTV) with 2,875 tCO2e. As a result, lower energy usage will lead to less carbon emissions that could provide a better environment, with less pollution and significantly lower cost.